Bacteriophage-fused peptides for serodiagnosis of human strongyloidiasis. - Nágilla Daliane Feliciano; Vanessa da Silva Ribeiro; Fabiana de Almeida Araújo Santos; Patricia Tiemi Fujimura; Henrique Tomaz Gonzaga; Luiz Ricardo Goulart; Julia Maria Costa-Cruz (Public Library of Science (PLoS), 2014)
BACKGROUND:Strongyloidiasis, a human intestinal infection caused by the nematode Strongyloides stercoralis, is frequently underdiagnosed and although its high prevalence is still a neglected parasitic disease because conventional diagnostic tests based on parasitological examination (presence of Strongyloides larvae in stool) are not sufficiently sensitive due to the low parasitic load and to the irregular larval output. There is an urgent need to improve diagnostic assays, especially for immunocompromised patients with high parasitic load as consequence of self-infection cycle, which can disseminate throughout the body, resulting in a potentially fatal hyperinfection syndrome often accompanied by sepsis or meningitis. METHODS/PRINCIPAL FINDINGS:We have performed Phage Display technology to select peptides that mimic S. stercoralis antigens, capable of detecting a humoral response in patients with strongyloidiasis. The peptides reactivity was investigated by Phage-ELISA through different panels of serum samples. We have successfully selected five peptides with significant immunoreactivity to circulating IgG from patients' sera with strongyloidiasis. The phage displayed peptides C9 and C10 presented the highest diagnostic potential (AUC>0.87) with excellent sensitivity (>85%) and good specificity (>77.5%), suggesting that some S. stercoralis antigens trigger systemic immune response. CONCLUSIONS/SIGNIFICANCE:These novel antigens are interesting serum biomarkers for routine strongyloidiasis screenings due to the easy production and simple assay using Phage-ELISA. Such markers may also present a promising application for therapeutic monitoring.